ANALISIS USABILITY DALAM USER EXPERIENCE PADA WEBSITE AYOSPORTS MENGGUNAKAN USE QUESTIONNAIRE - Rivaldo Winengko; Junaedy; Izmy Alwiah Musdar (KHARISMA Tech, 2021)
This research aims to test the usability level of the Ayosports website based on user experience using the USE Questionnaire method. This method has 4 aspects, namely Usefullness, Ease of Use, Ease of Learning, and Satisfaction. The study began by using questionnaires as a data collection tool, then continued by testing the validity of the data to analyze the data resulting in 24 items of questions worth processing. After that, it continued by testing the data rehabilitation of 24 question items by generating a Cronbach's Alpha value of 0.955. The results of this study include 4 aspects of use questionnaire, in the form of usefullness aspect with a percentage of 83.73%, ease of use aspect with a percentage of 82.59%, ease of learning aspect with a percentage of 82.22%, and satisfaction aspect with a percentage of 80.67%. Thus, for the overall results of this study has a percentage of 82.22%, so it can be concluded that the Ayosports website has met the standards or criteria in the USE Questionnaire aspect.